Teachers' Roles in Preserving Sundanese Pupuh in Grade 5 Elementary Classroom: A Qualitative Case - Ria Asyifah Riyani; Rifky Aditya Ramadhan; Efi Kurniasari (MASI Mandiri Edukasi, 2026)
Preserving local culture in elementary education faces challenges due to limited integration of traditional arts into formal classroom instruction. Sundanese pupuh, as a form of oral literature rich in cultural and character values, requires active transmission through educational practices to remain sustainable. This study aims to examine the role of teachers in preserving Sundanese pupuh through Art and Culture learning in a Grade V elementary classroom. This study employed a descriptive qualitative approach with a case study design. The research was conducted at an elementary school in Sukabumi Regency, West Java, involving a Grade V teacher as the primary participant. Data were collected through classroom observations, semi-structured interviews, and documentation of Art and Culture learning activities. Data analysis followed an interactive model consisting of data collection, data reduction, data display, and conclusion drawing. The findings indicate that Sundanese pupuh was integrated into classroom learning through structured activities, including the introduction of pupuh types, explanation of lyrical meanings, and guided practice. Teachers played a key role as cultural mediators by facilitating learning, motivating students, and integrating cultural and character values. Student engagement in pupuh learning was generally positive and supported cultural awareness and character development. This study is limited by its focus on a single school context and the absence of long-term analysis of students’ cultural identity development. The findings suggest that strengthening teacher competence and providing institutional support are essential for sustaining local culture-based learning in elementary education.